Tissue Engineered Materials in Cardiovascular Surgery: The Surgeon's Perspective - Durko, Andras P.; Yacoub, Magdi H.; Kluin, Jolanda (Frontiers in Cardiovascular Medicine, 2020)
In cardiovascular surgery, reconstruction and replacement of cardiac and vascular structures are routinely performed. Prosthetic or biological materials traditionally used for this purpose cannot be considered ideal substitutes as they have limited durability and no growth or regeneration potential. Tissue engineering aims to create materials having normal tissue function including capacity for growth and self-repair. These advanced materials can potentially overcome the shortcomings of conventionally used materials, and, if successfully passing all phases of product development, they might provide a better option for both the pediatric and adult patient population requiring cardiovascular interventions. This short review article overviews the most important cardiovascular pathologies where tissue engineered materials could be used, briefly summarizes the main directions of development of these materials, and discusses the hurdles in their clinical translation.